Synthesis of the Polymorphic Forms of Clopidogrel Hydrogen Sulfate Through Reactive Crystallization and Transformation - Lu, J.; Chen, L.W.; Wang, J.; Li, Z. (Asian Journal of Chemistry, 2012)
This work reports the preparation, solid state characterization and solvent-mediated transformation of the amorphous, I and II forms of clopidogrel hydrogen sulfate. In particular, labile precipitate and oiling out occurring in the reactive crystallization of clopidogrel hydrogen sulfate are firstly reported and analyzed. The occurrence domains of three forms are also schematically outlined as well. These results will contribute to a better understanding about the polymorphic nature of clopidogrel hydrogen sulfate, together with the approaches to synthesizing its pure forms.